France : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
This note estimates potential output for France during 1980-2010, using three distinct approaches, and discusses long-term growth prospects. The focus on capital taxation highlights the need for a broader reform of the French tax system to address the features that hamper job growth, investment, and productivity growth. This paper analyzes the impact of Basel III capital requirements on French banks and the French economy, and proposes policy recommendations. French banks should be able to meet the new requirements through earnings retention.